2022
DOI: 10.1002/adem.202200959
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior and Sensing Properties of Bio‐Based Conductive Composite Materials

Abstract: Poly(3‐hydroxyoctanoate) (PHO), a biocompatible polymer with a skin‐like feel produced by bacterial fermentation, is compounded with carbon nanofibers (CNFs) or carbon black (CB), respectively, to form flexible, 3D printable, bio‐based conductive composites. Conductivities up to 10 and 3 S m−1 can be achieved for CNF and CB, respectively, without negatively affecting the composites’ processability. Both filler materials act as nucleating agents for PHO crystallization, significantly accelerating this process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Most of these devices contain metals (e.g., silver, copper) and fossil-based materials (e.g., printed circuit board), meaning that the end-of-life and toxicity of these devices can become an issue. To solve this problem green or sustainable electronics are being developed to ameliorate these environmental issues . Typical strategies include the substitution of metal-based conductive inks/materials with sustainably sourced carbon-based conductive materials, such as graphene or carbon nanomaterials, and replacing the body of the device/substrate with biodegradable polymers or natural materials to reduce its impact on the environment. Recently, Beniwal et al have showed that graphene-based carbon ink could be screen-printed onto a paper substrate to construct a humidity sensor with wireless communication . Additionally, Tu et al have showed that carbon-based inks could be printed onto dissolvable PVA/gelatin substrates for point-of-care testing .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these devices contain metals (e.g., silver, copper) and fossil-based materials (e.g., printed circuit board), meaning that the end-of-life and toxicity of these devices can become an issue. To solve this problem green or sustainable electronics are being developed to ameliorate these environmental issues . Typical strategies include the substitution of metal-based conductive inks/materials with sustainably sourced carbon-based conductive materials, such as graphene or carbon nanomaterials, and replacing the body of the device/substrate with biodegradable polymers or natural materials to reduce its impact on the environment. Recently, Beniwal et al have showed that graphene-based carbon ink could be screen-printed onto a paper substrate to construct a humidity sensor with wireless communication . Additionally, Tu et al have showed that carbon-based inks could be printed onto dissolvable PVA/gelatin substrates for point-of-care testing .…”
Section: Introductionmentioning
confidence: 99%